Synopsis of Pseudacroclita Oku from China, with descriptions of two new species (Lepidoptera: Tortricidae) - Zhang, Aihuan (Zootaxa, 2018)
Six species of Pseudacroclita Oku are reported from China, two of which are described as new: P. damingshana, sp. nov., and P. mastoidea, sp. nov. Photographs of the adults and genitalia of the two new species are provided. Two keys to Chinese species of Pseudacroclita are given, one based on male genitalia and the other on female genitalia. Non-deciduous spiculate cornuti in the phallus are reported for the first time in Pseudacroclita. All specimens examined are deposited in the Insect collection, Nankai University, Tianjin, China.